Workshop Penulisan Proposal dan Laporan Karya Ilmiah untuk Dosen dan Mahasiswa - Revi Lestari Pasaribu; Asep Nursangaji; Ade Mirza; Yulis Jamiah; Silvia Sayu (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
This PKM activity started from the interest of lecturers at the Mathematics Education Study Program at Tanjungpura University to write proposals and reports for lecturers and students in West Kalimantan following the regulations of the Ministry. The form of this PKM is a workshop with the title "Workshop on Proposal Writing and Scientific Work Reports for Lecturers and Students at STKIP Singkawang." This workshop was attended by 25 people consisting of lecturers and final semester students at STKIP Singkawang. The data collection technique is observation, interview, and documentation. The PKM activity plans are 1) Preparation: determining the location and obtaining an implementation permit in this workshop activity; 2) Implementation: conducting workshops, analyzing test results, and assisting in the preparation and preparation of scientific article publications, conducting workshops in class; 3) Final: The making of this scientific proposal and report produces a scientific paper proposal and report. The result of this PKM is the implementation of the Workshop on Writing Proposals and Scientific Work Reports for Lecturers and Students following the steps that have been determined and the proposals and scientific reports of STKIP Singkawang lecturers.